2019
DOI: 10.1177/1120672119893291
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser–assisted cataract surgery: A review

Harry W Roberts,
Alexander C Day,
David PS O’Brart

Abstract: Purpose: Review scientific literature concerning femtosecond laser–assisted cataract surgery. Methods: Following databases were searched: CENTRAL (Cochrane Eyes and Vision Trials Register; Cochrane Library: Issue 2 of 12, June 2019), Ovid MEDLINE® without Revisions (1996 to June 2019), Ovid MEDLINE® (1946 to June 2019), Ovid MEDLINE® Daily Update June 2019, MEDLINE and MEDLINE Non-Indexed Items, Embase (1980–2019), Embase (1974 to June 2019), Ovid MEDLINE® and Epub Ahead of Print, in-Process & Other Non-In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 121 publications
1
32
0
1
Order By: Relevance
“… 79 While it offers potential advantages in terms of automation of some of the surgical steps of cataract surgery, clinical outcomes appear to be no better than those with PCS. 80 , 81 At present there is limited evidence on the long-term effects of FLACS on the ocular surface, although there are a number of studies which indicate that akin to PCS, FLACS also leads to signs and symptoms of DED. 82 , 83 …”
Section: The Pathophysiology Of Cataract Surgery Associated Dedmentioning
confidence: 99%
“… 79 While it offers potential advantages in terms of automation of some of the surgical steps of cataract surgery, clinical outcomes appear to be no better than those with PCS. 80 , 81 At present there is limited evidence on the long-term effects of FLACS on the ocular surface, although there are a number of studies which indicate that akin to PCS, FLACS also leads to signs and symptoms of DED. 82 , 83 …”
Section: The Pathophysiology Of Cataract Surgery Associated Dedmentioning
confidence: 99%
“…The prevalence of clinically significant cataract is about 93 percent in patients aged 80 or older and influenced the visual function of approximately 95 million people in 2014 [ 2 ]. The current management of visually disturbed cataract is via surgery, such as phacoemulsification or manual small-incision cataract surgery [ 3 , 4 ], and the femtosecond laser device can be applied in certain cases [ 5 , 6 ]. Although the general success rate is high for cataract surgery, certain visual-threatening complications can still occur, including cystoid macular edema, pseudophakic bullous keratopathy, retinal detachment, and postoperative endophthalmitis [ 1 , 2 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] This study demonstrates that although femtosecond laser made the surgical steps of cataract surgery more predictable, it still has to be further studied in large multicenter studies to justify the benefits against the high cost of the technology, particularly many recent studies concluded that there was no statistically significant difference between FLACS and standard phacoemulsification in terms of visual outcomes and complications. [30][31][32]…”
Section: Discussionmentioning
confidence: 99%